A micromechanical model for the dynamic behavior of porous media in the void coalescence stage. (1st October 2015) - Molinari, Alain; Jacques, Nicolas; Mercier, Sébastien; Leblond, Jean-Baptiste; Benzerga, A. Amine
Highlights: A complete model of dynamic void coalescence is proposed for the first time. A cylindrical unit-cell model is developed which accounts for necking of intervoid ligaments. The contributions of micro-inertia, material properties and cell geometry to the overall flow stress are rationalized. The overall flow stress is characterized by analytical means. Analytical results are compared against unit-cell finite element calculations. Abstract: Micro-inertia effects have been included in a micro-mechanical model of void coalescence by necking of intervoid ligaments. A hollow cylindrical unit-cell model is considered. Inertia effects at the scale of the unit-cell are quantified by using a dynamic homogenization approach for porous materials combined with trial velocity fields. The effects of micro-inertia on the effective flow stress (overall apparent stress) are characterized by analytical means and are shown to be significant at high loading rates. The roles of cell configuration and loading conditions are analyzed in details. The agreement with finite element simulations is found to be quite satisfactory in the range of validity of the proposed model. This approach of dynamic void coalescence is aimed to improve the modeling of the dynamic failure of ductile materials subjected to high strain rates.